Transforming care in Cornwall: A review of the quality of the lives of people with learning disabilities a decade post‐discharge from hospital. (15th January 2020) - Niven, Abigail; Gamman, Lee; Webb, Alison; Goodey, Rebecca; Shankar, Rohit
Accessible summary: The government wants people with learning disabilities and/or autism to move out of hospitals back to their homes. Cornwall did this in 2007, and we asked the people who moved and their carers how they are now. They have generally done well, and nearly all have stayed in their homes with lots of support. Various factors such as accommodation, social network, skill acquisition and impact of their past were explored. Abstract: Background: In the light of the current national guidance to reduce the number of inpatient learning disability beds, a review was completed of the quality of lives of the people who had been former inpatients in Cornwall at the time of closure of the learning disability inpatient facilities almost 10 years before transforming care. Materials and Methods: All former inpatients who were discharged from the learning disability inpatient setting in Cornwall were invited to participate either directly or through their carers or family members. Measures of current activity levels and semi‐structured interviews on quality of life were conducted. Results: The majority interviewed had person‐centred plans, health action plans and positive behaviour support plans. Guernsey Community Participation & Leisure Assessment showed overall the study group did not meet comparative standards laid out by the scale in any of the subdomains ( p  < .05). Peoples' lives were varied, with a lack of informal relationships, meaningful occupation, homeownership and advocacy being relatively poor for all. Alongside this, to enable people to have safer lives, restrictive practices were commonplace particularly continuous supervision and use of psychotropic medication to manage behavioural risk. Conclusions: This study highlights that people with complex concerns with a history of placement breakdowns and past institutionalisation can be settled successfully and safely in local communities. However, it is difficult for many of them to achieve a satisfactory quality of life long term. The obligation for this lies with service providers to provide adequate support to overcome that difficulty.